Implementation of the Land Dispute Peace Agreement Mediated by the National Land Agency of Jayapura Regency - Yosafat Siolemba; Muslim Muslim; Zonita Zirhani Rumalean (COMPENDIUM OF JUDGE MADE LAW, 2025)
The National Land Agency (BPN) as a government agency has been given authority by laws and regulations in the field of land in resolving land disputes or conflicts. The Process of Resolving Land Disputes and Conflicts according to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 11 of 2016 BPN as a mediator in resolving land disputes Settlement of Land Disputes and Conflicts in this ministerial regulation is also carried out based on 2 things, namely the initiative of the ministry and public complaints Dispute resolution, in this case civil disputes can be carried out either conventionally through the courts (litigation) or through alternative dispute resolution mechanisms outside the courts (non-litigation). peace outside the courts is the basis for handling land dispute resolution by BPN through mediation.